Sjögren’s syndrome is associated with a reduction in the surface area of the right caudal anterior cingulate gyrus - Ping Wang; Yunpeng Tai; Xiaofang Zhu; Xinyi Wan; An Sun; Jiajia Wang; Hui Cheng; Jingwei Hong; Yi Zhang; Xiaobing Wang (BMC Medicine)
Abstract Background Sjögren’s syndrome (SS) is a common chronic autoimmune disease. Neurological involvement in SS represents one of the more severe and challenging aspects, with complications affecting the central system leading to cognitive dysfunction, sensory neuropathy, and multifocal sensorimotor neuropathies among other cortical function abnormalities. The relationship between cerebral cortex structure and neurological pathologies is well-documented, yet the impact of SS on cerebral cortex structure remains unclear. Methods A two-sample Mendelian randomization (MR) analysis was conducted using four single-nucleotide polymorphisms (SNPs) associated with SS. Summary data from genome-wide association studies (GWAS) on SS and brain cortical structure were analyzed using inverse-variance weighted (IVW), MR-Egger, and weighted median (WM) methods. Sensitivity analyses were performed to ensure reliability. Brain magnetic resonance imaging (MRI) scanning of a group of established but treatment-naïve SS patients were performed and assessed for validation. For TWAS (transcriptome-wide association studies), we used the RNA sequencing expression data from the Genotype-Tissue Expression version 8 (GTEx v8) for the cerebral cortex as a reference dataset and predicted the mRNA expression levels of cis-regulated genes in the cerebral cortex using linear models based on expression quantitative trait loci (eQTLs). We also used CELLECT to leverage genome-wide association study (GWAS) and single-cell RNA sequencing (scRNA-seq) data to identify pathogenic cell types. Results The MR analysis revealed a negative genetic causal relationship between SS and brain structure (entorhinal: IVW: beta = − 3.4398, SE = 1.6954, P = 0.0425; caudal anterior cingulate gyrus: IVW: beta = − 4.2947, SE = 2.0593, P = 0.0370). Brain MRI of SS patients confirmed a reduction in the surface area of the right caudal anterior cingulate. TWAS identified genes associated with SS in the major histocompatibility complex (MHC) region and identified PRTFDC1 in the caudal anterior cingulate gyrus. Cell-type enrichment analysis indicated that excitatory glutamatergic cells are primarily involved in the brain changes associated with SS. Conclusions This study suggests that SS is a risk factor for changes in brain cortical structure, with a reduction in the surface area of the right caudal anterior cingulate gyrus. The identified genes and cell types provide insights into the mechanisms underlying the effects of SS on brain structure.